International organizations : politics, law, practice - Hurd, Ian. (Cambridge, UK : Cambridge University Press, 2011)
'International organizations are at the heart of many global issues today. This new textbook looks at the leading international organizations and explains how they both shape and are shaped by international politics. The book examines three themes: the legal obligations that give international organizations their powers; the mechanisms that elicit compliance by their member states; and the practices of enforcement in the organizations. Each chapter shows how international organizations work in practice and the interactions between them and their member states. This fresh text provides a comprehensive understanding of what international organizations do, how and why they do it, and the challenges they face'--
Includes bibliographical references and index.
Keywords: International agencies; International organization